2004
DOI: 10.1111/j.1741-2358.2004.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional training of dysphagia to prevent pneumonia for patients on tube feeding

Abstract: It was suggested that once-a-week functional training of dysphagia with professional oral care might be effective in preventing pneumonia for elderly people who were being tube fed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 7 publications
1
24
0
1
Order By: Relevance
“…Oral function maintenance has been considered crucial in the course of life . Various exercise programmes for oral function have been developed for older people and practised in numerous areas in Japan, and many studies have confirmed the effectiveness of these exercise programmes . In addition, promotion of oral function was able to improve general health, including protection of the respiratory organs, improvement of nutritional status, decrease of infections and enhancement of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Oral function maintenance has been considered crucial in the course of life . Various exercise programmes for oral function have been developed for older people and practised in numerous areas in Japan, and many studies have confirmed the effectiveness of these exercise programmes . In addition, promotion of oral function was able to improve general health, including protection of the respiratory organs, improvement of nutritional status, decrease of infections and enhancement of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The identification and management of dysphagia are important to minimise the risk of infection (usually because of poor mouth care) [5, 6], distress due to aspiration of food and liquids and the ability to provide adequate calories.…”
Section: Introductionmentioning
confidence: 99%
“…However the influence of food texture designed by mechanical test and sensory evaluation [12] on eating behavior (that is, oral strategy) has yet to be clarified. In dysphagic patients, not only the oral stage, but also the pharyngeal stage is often adversely affected by the collapse of coordination between tongue and jaw movements or tongue disability [13]. As many soft foods are assumed to be eaten under integrated oral strategies such as mastication and squeezing, with the comminuted or crushed bolus propelled into the pharynx by the driving force of the tongue in the final swallow [14][16], clarification of the influence of food texture on tongue kinetics in the oral strategy would presumably be useful in designing food texture for dysphagic patients.…”
Section: Introductionmentioning
confidence: 99%